Voices of Malvinas: Service-Learning for Memory and Sovereignty - María Sofía Vassallo (Perspectivas Metodológicas​)
This article presents the service-learning experience developed in Voces de Malvinas. Archive of the Memories of the Combatants, a research project initiated and based at the Malvinas Observatory, under the Secretariat of Research and Graduate Studies at the National University of Lanús (UNLa). The project involves the recording, study, and preservation of the testimonies of Argentine protagonists of the 1982 war. At both UNLa and UNA, it is led by students who respond to the need for listening, recognition, and remembrance of war veterans, through the application of knowledge and skills acquired in their respective degree programs.